2010
DOI: 10.1016/j.bbabio.2010.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Possible roles of two quinone molecules in direct and indirect proton pumps of bovine heart NADH-quinone oxidoreductase (complex I)

Abstract: In many energy transducing systems which couple electron and proton transport, for example, bacterial photosynthetic reaction center, cytochrome bc1-complex (complex III) and E. coli quinol-oxidase (cytochrome bo3 complex), two protein-associated quinone molecules are known to work together. T. Ohnishi and her collaborators reported that two distinct semiquinone species also play important roles in NADH-ubiquinone oxidoreductase (complex I). They were called SQNf (fast relaxing semiquinone) and SQNs (slow rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…In contrast, in complex I the electron and proton transfers are separated both kinetically and spatially. To explain this long-range coupling, both "direct" (redox-driven) and "indirect" (conformational-driven) mechanisms have been suggested, but the molecular principles of these mechanisms remain elusive (1,2,4,(17)(18)(19)(20)(21)(22).…”
Section: Significancementioning
confidence: 99%
“…In contrast, in complex I the electron and proton transfers are separated both kinetically and spatially. To explain this long-range coupling, both "direct" (redox-driven) and "indirect" (conformational-driven) mechanisms have been suggested, but the molecular principles of these mechanisms remain elusive (1,2,4,(17)(18)(19)(20)(21)(22).…”
Section: Significancementioning
confidence: 99%
“…The majority of stoichiometry measurements have been carried out on the mammalian enzyme (see, for example [1][2][3]) for which the four-protonsper-NADH stoichiometry is relatively well established: it is possible that mammalian complexes I pump two protons per catalytic half cycle (one through subunit ND4 and one through ND5), whereas fungal and bacterial complexes I may pump three (through subunits ND4, ND5 and ND2). Whether ND2 is directly active in proton translocation is thus a key fact in distinguishing extant mechanistic models for proton translocation by complex I (for example, [10,34]). Interestingly, it has been found recently that the c-ring of ATP synthase contains only eight subunits in vertebrates, and probably in many invertebrates, but between 10 and 15 subunits in fungi and eubacteria [37].…”
Section: Possible Implications For the Mechanism Of Complex Imentioning
confidence: 99%
“…Possible supporting roles include anchoring the lateral helix and promoting the coupling of proton and electron translocation, and ND2 has been suggested to bind ubiquinone also [23,34]. It is interesting to note that both the operation of the 'active-deactive transition' in complex I from higher metazoans, and the high affinity of these enzymes for rotenone [35,36], may be related to the truncation of ND2, although there is insufficient extant data for a definitive correlation to be drawn at present.…”
Section: Possible Implications For the Mechanism Of Complex Imentioning
confidence: 99%
“…1) (8,11). Biochemical and structural studies suggest that the reduction of Q activates the proton pump via a conformationaldriven coupling mechanism, accompanied by electrostatic gating (2, 6-8, [12][13][14]. A recent study suggested that water-gated transitions and cooperative electrostatic couplings are also of importance in establishing a functional pump (15).…”
mentioning
confidence: 99%
“…chain, thus allowing for efficient eT (13,18 and references therein). This finding is consistent with earlier biochemical data, suggesting that the Q headgroup is in hydrogen-bonding contact with Tyr-87 of subunit Nqo4 (19).…”
mentioning
confidence: 99%